Data for: The polar transition from alpha to beta regions set by a surface buoyancy flux inversion - Caneill, Romain (University of Gothenburg, 2024)
Dataset related to a study that investigates how the location of the polar transition (between alpha and beta ocean) and of the intermediate water location are influenced by the surface buoyancy flux, and especially by its latitudinal change of sign. As the buoyancy flux is strongly linked to the TEC in the polar area, modifying the parameters for the EOS in a numerical model study is used here as an effective method to modulate the relative impact of heat and freshwater on the surface buoyancy flux. The stratification is also impacted, while keeping similar surface temperature and salinity fields and the same wind forcing between the experiments. For the numerical experiments, an idealized configuration of the NEMO (Nucleus for European Modeling of the Ocean; Madec et al. 2019) ocean general circulation model (OGCM) has then been developed, using a simplified EOS allowing for a full control of its nonlinearities

Data tillhörande studie var syfte var att undersöka hur läget för den polära övergången (mellan alfa- och betahav) och för det mellanliggande vattnets läge påverkas av flytkraftsflödet på ytan. För mer detaljerad information se engelsk beskrivning nedan.
Data för: Den polära övergången från alfa- till betaregioner som bestäms av en inversion av ytuppdriftsflödet
Keywords: OCEAN CIRCULATION; stratification; lagring; seawater; havsvatten; buoyancy; thermal expansion; Cabbeling effect; Cabbelingeffekt; alpha ocean; alfa hav; thermal expansion coefficient; termisk expansionskoefficient; surface flux; ytflöde; intermediate waters; mellanvatten; beta ocean; beta hav; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser